Diversity of parasitic Hymenoptera in three rice-growing tracts of Tamil Nadu, India - Johnson Alfred Daniel; Kunchithapatham Ramaraju (Journal of Threatened Taxa, 2019)
Parasitic hymenoptera play a vital role in rice ecosystems as biocontrol agents of pests.  Surveys were conducted from August 2015 to January 2016 in three rice growing zones in Tamil Nadu: western zone, Cauvery Delta zone, and high rainfall zone.  A total of 3,151 parasitic hymenoptera were collected, of which 1,349 were collected from high rainfall zone, 1,082 from western zone, and 720 from Cauvery Delta zone.  Platygastridae, Ichneumonidae, and Braconidae were the most abundant families in all the three zones.  The species diversity, richness, evenness as well as beta diversity were computed for all three zones via Simpson’s, Shannon-Wiener and Margalef indices.  The results showed the high rainfall zone to be the most diverse and the Cauvery Delta zone the least diverse, but with more evenness.  Pairwise comparison of zones using Jaccard’s index showed 75–79% species similarity.